Endoscopic Endonasal Clipping of Anterior Circulation Aneurysm: Surgical Techniques and Results - Xiao, Li-Min; Tang, Bin; Xie, Shen-Hao; Huang, Guan-lin; Wang, Zhi-Gang; Zeng, Er-Ming; Hong, Tao (World neurosurgery, 2018)
Endoscopic endonasal clipping of intracranial aneurysms may use microsurgical techniques as an alternative to the transcranial approach. Here we report a series of patients who underwent microsurgical clipping of anterior circulation aneurysms via an endoscopic endonasal approach (EEA). This retrospective chart review included all the patients who underwent standard binostril EEA for aneurysm clipping. Surgical outcomes and complications are noted. The rationality and limitations of this procedure are discussed. Seven patients with 12 aneurysms of the anterior circulation underwent EEA for clipping. These 12 aneurysms consisted of 5 anterior communicating artery (AComA) aneurysms, 4 paraclinoid aneurysms, 1 ophthalmic artery aneurysm, and 2 aneurysm located in the cavernous segment of internal carotid artery (ICA). Nine of the 12 aneurysms were successfully clipped. One giant paraclinoid aneurysm could not be clipped during operation and was coiled in second endovascular stage. The 2 aneurysms located in the cavernous segment of ICA were not clipped intentionally in a single-stage procedure, after weighing the surgical benefit against the difficulty of surgical exposure and feasibility. The proximal control of ICA was achieved in all cases. There was no death, no cerebrospinal fluid leak, or other complications. All patients recovered completely. EEA can provide direct access for microsurgical clipping of strictly selected anterior circulation aneurysms. All the principles of cerebrovascular surgery must be followed. These procedures require a long learning curve. Only teams with adequate experience in microvascular and endoscopic skull base surgeries should attempt this approach for treating aneurysms. •Seven patients with 12 aneurysms (among the largest series) of the anterior circulation underwent clipping via an EEA.•Nine of the 12 aneurysms were successfully clipped.•There were no deaths and no CSF leak or other complications.•The EEA can provide direct access for microsurgical clipping of rare and strictly selected anterior circulation aneurysms.